Multimedia-Based Geometry Education for Elementary School Students - Hari Suryantoro (Jurnal Ekspresi : Desain Komunikasi Visual dan Seni, 2023)
This study is concerned with the creation of interactive multimedia for elementary school geometry instruction in an effort to enhance students' comprehension. Considering the criticality of technology integration in the realm of education, interactive multimedia presents a novel and efficacious approach to imparting academic content. Interactive multimedia, comprising video, text, images, sound, animation, and animation, enables students to comprehend and visualize geometric concepts in a real-world setting, thereby promoting active and interactive learning. As technology progresses, interactive multimedia becomes increasingly affordable and accessible, facilitating both independent learning and online teacher-student interaction. This research develops and implements interactive multimedia using the ADDIE model, beginning with a requirements assessment and concluding with an implementation evaluation. The findings indicate that the incorporation of interactive multimedia can increase students' comprehension and interest in geometry, as well as enrich the learning experience.